Respuesta :

a) The gravitational force between the Earth and the Moon is [tex]1.98\cdot 10^{20} N[/tex]

b) The acceleration of the Moon is [tex]2.70\cdot 10^{-3} m/s^2[/tex]

c) The acceleration of gravity on the Moon is [tex]1.62 m/s^2[/tex], and the weight of a person on the moon is [tex]W=1.62 m[/tex] [N]

Explanation:

a)

The gravitational force between the Earth and the Moon is given by:

[tex]F=G\frac{m_e m_m}{r^2}[/tex]

where

[tex]G=6.67\cdot 10^{-11} m^3 kg^{-1}s^{-2}[/tex] is the gravitational constant

[tex]m_e = 5.97\cdot 10^{24} kg[/tex] is the mass of the Earth

[tex]m_m = 7.34 \cdot 10^{22} kg[/tex] is the mass of the Moon

[tex]r=3.84\cdot 10^8 m[/tex] is the distance between the Earth and the Moon

Substituting the values, we find:

[tex]F=(6.67\cdot 10^{-11})\frac{(5.97\cdot 10^{24})(7.34\cdot 10^{22})}{(3.84\cdot 10^8)^2}=1.98\cdot 10^{20} N[/tex]

b)

We can find the Moon's acceleration by using Newton's second law:

[tex]F=m_m a[/tex]

where:

[tex]F=1.98\cdot 10^{20} N[/tex] is the net force exerted on the Moon by the Earth

[tex]m_m = 7.34 \cdot 10^{22} kg[/tex] is the mass of the Moon

a is the acceleration of the Moon

Re-arranging the equation,

[tex]a=\frac{F}{m_m}[/tex]

And solving,

[tex]a=\frac{1.98\cdot 10^{20}}{7.34\cdot 10^{22}}=2.70\cdot 10^{-3} m/s^2[/tex]

c)

We start by calculating the acceleration of gravity (g) on the Moon, which is given by

[tex]g_m = \frac{Gm_m}{R^2}[/tex]

where:

[tex]G=6.67\cdot 10^{-11} m^3 kg^{-1}s^{-2}[/tex] is the gravitational constant

[tex]m_m = 7.34 \cdot 10^{22} kg[/tex] is the mass of the Moon

[tex]R=1740 km = 1.74\cdot 10^6 m[/tex] is the radius of the Moon

Substutiting,

[tex]g_m = \frac{(6.67\cdot 10^{-11})(7.34\cdot 10^{22})}{(1.74\cdot 10^6)^2}=1.62 m/s^2[/tex]

And therefore, the gravitational force of a person of mass m standing on the surface of the Moon is:

[tex]W=mg_m = 1.62 m[/tex] [N]

Learn more about gravitational force:

brainly.com/question/1724648

brainly.com/question/12785992

#LearnwithBrainly